Solid state anaerobic digestion of water poor feedstock for methane yield: an overview of process characteristics and challenges - Paritosh, Kunwar; Kumar, Vinod; Pareek, Nidhi; Sahoo, Dinabandhu; Bajón Fernández, Yadira; Coulon, Frederic; Radu, Tanja; Kesharwani, Nupur; Vivekanand, Vivekanand (Springer, 2021)
Solid state anaerobic digestion (SSAD) of water poor feedstock may be a promising technology for energy recovery. Feedstocks having high solid concentration like lignocellulosic biomass, crop residues, forestry waste and organic fraction of municipal waste may be the appropriate feedstock for its biochemical conversion into energy carries like biomethane through SSAD. Compared to liquid state anaerobic digestion (LSAD), SSAD can handle higher organic loading rates (OLR), requires less water and smaller reactor volume and may have lower energy demand for heating or stirring and higher volumetric methane productivity. Besides these, pathogen inactivation may also be achieved in SSAD of biodegradable waste. Around 60% of recently built AD systems have adopted SSAD technology. However, the process stability of an SSAD system may have several constraints like limited mass transfer, process inhibitors and selection of digester type and should be addressed prior to the implementation of SSAD technology. In this article, a comprehensive overview of the key aspects influencing the performance of SSAD is discussed along with the need for mathematical modelling approaches. Further to this, reactor configuration for SSAD and digestate management requirement and practice for solid-state condition are reviewed for a better insight of SSAD technology.
Keywords: Biomass; Solid state anaerobic digestion; Clean energy; Mathematical modelling; Digestate management; Biogas